The impact of depression at preconception on pregnancy planning and unmet need for contraception in the first postpartum year: a cohort study from rural Malawi - Raquel Catalao; Hilda Chapota; Genesis Chorwe-Sungani; Jennifer Hall (BMC, 2023)
Plain language summary Family planning programmes have traditionally focused on increasing access to modern contraceptive methods. There is growing evidence that merely increasing access will not reach every woman. More focus on improving the quality of the family planning programmes and developing targeted interventions for women and men not currently reached with the current models is necessary. Despite the high prevalence of depression in women of reproductive age living in LMICs, its impact on women's access and use of contraception has been largely neglected. Our study using data from a cohort of pregnant women recruited in rural Malawi aimed to investigate if depression in the year before pregnancy impacted on women's risk of having an unintended pregnancy and on contraceptive use at time of pregnancy and in the postpartum period. Our results show that women who reported depression in the year before pregnancy had increased risk of inconsistent contraceptive use and having an unplanned pregnancy. They were also more likely to not use contraception in the early postpartum period and choose less effective methods, with important consequences for risk of subsequent unplanned pregnancies. Our results highlight a need for health services to develop holistic models of care for women where both their mental and reproductive health needs are met.